Usefulness of Quantitative Endotracheal Aspirate Cultures in Intensive Care Unit Patients with Suspected Pneumonia - Shin, Yoon Mi; Oh, Yeon-Mok; Kim, Mi Na; Shim, Tae Sun; Lim, Chae-Man; Lee, Sang Do; Koh, Younsuck; Kim, Woo Sung; Kim, Dong Soon; Hong, Sang-Bum (Journal of Korean medical science, 2011)
It is difficult to differentiate pathogens responsible for pneumonia or colonization in patients with an endotracheal tube or in patients that have undergone tracheostomy. We evaluated the clinical usefulness of quantitative endotracheal aspirates cultures and sought to determine the result threshold level for positivity. The authors performed this retrospective cohort study between December 1, 2004 and January 31, 2006. Forty-five suspected pneumonia patients admitted to an intensive care unit (ICU) with quantitative bronchoalveolar lavage (BAL) and endotracheal aspirate (EA) culture results were enrolled. Using a threshold of 10(5) cfu/mL, 10 of the 45 (22.2%) quantitative EA cultures were positive, as compared with 7 (15.6%) BAL cultures. When BAL culture findings were used as the reference, the sensitivity and specificity of quantitative EA cultures were 85.7% and 89.5%, respectively, at a threshold of 10(5) cfu/mL, and 85.7% and 94.7%, respectively, at a threshold of 10(6) cfu/mL. Of the 10 EA culture positive patients, 2 patients with a result of -10(5) cfu/mL were BAL culture negative. The quantitative EA culture is a useful non-invasive tool for the diagnosis of pneumonia pathogens. It is suggested that a threshold level of 10(6) cfu/mL is appropriate.